A practical guide to managing hypertension, hyperlipidemia, and hyperglycemia in patients with chronic myeloid leukemia - Khalid Ahmed; Rasha Kaddoura; Mohamed A. Yassin (Frontiers in Medicine, 2022)
Tyrosine kinase inhibitors (TKIs) have significantly improved the prognosis of chronic myeloid leukemia (CML) since their approval. Although safe in general, TKIs carry concerns about cardiovascular adverse events. Hypertension, diabetes, and dyslipidemia are among the most common baseline comorbidities among CML patients. Guidelines for the management of the existing comorbidities or those related to TKI therapy are lacking. This paper will review hypertension, hyperglycemia and hyperlipidemia reported in CML patients or associated with TKI therapy and then propose a simple guide on their management.